2022
DOI: 10.1111/jai.14324
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Brachymystax and Hucho genera—Summary on evolutionary status within the Salmoninae subfamily

Abstract: The family Salmonidae (salmonids) represents an economically and ecologically important freshwater fish group that attracted considerable research attention due their interesting biological features, such as: the tendency to hybridization, a tetraploid origin, high ecological and behavioral diversity as well as wide biographical distribution.The family encompasses more than 200 species distributed over 11 extant genera, which are assigned to three subfamilies, namely: (1) Coregoninae, (2) Thymallinae and (3) S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 74 publications
4
1
0
Order By: Relevance
“…The topology inner Salmoninae we inferred was consistent with other studies, the Hucho and Brachymystax formed the ancient branch of the subfamily salmoninae, and constituted the sister group to the genera Salmo, Salvelinus and Oncorhynchus (Crespi and Fulton 2004;Kucinski and Fopp -Bayat 2022). The estimated divergence time based on nuclear genome was similar to the previous researches based on mitochondrial genome (Crête-Lafrenière, et al 2012;Horreo 2017;Kucinski and Fopp-Bayat 2022). The divergence time between the Hucho and Brachymystax was estimated at ~9.28 to ~17.96 Mya, which coincides with the Miocene Climate Optimum (MCO) at 15-18 Mya (Böhme 2003;Sun and Zhang 2008).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The topology inner Salmoninae we inferred was consistent with other studies, the Hucho and Brachymystax formed the ancient branch of the subfamily salmoninae, and constituted the sister group to the genera Salmo, Salvelinus and Oncorhynchus (Crespi and Fulton 2004;Kucinski and Fopp -Bayat 2022). The estimated divergence time based on nuclear genome was similar to the previous researches based on mitochondrial genome (Crête-Lafrenière, et al 2012;Horreo 2017;Kucinski and Fopp-Bayat 2022). The divergence time between the Hucho and Brachymystax was estimated at ~9.28 to ~17.96 Mya, which coincides with the Miocene Climate Optimum (MCO) at 15-18 Mya (Böhme 2003;Sun and Zhang 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Based on the phylogenetic tree constructed by the orthologous genes, we suggested that Coregoninae and Thymallinae had sister relationship which supported by 100% bootstraps, and was consistent with other trees based on orthologues (Macqueen and Johnston 2014; Robertson, et al 2017), mitochondrial genome (Campbell, et al 2013; Shedko, et al 2013), and ultra-conserved element (Campbell, et al 2020). The topology inner Salmoninae we inferred was consistent with other studies, the Hucho and Brachymystax formed the ancient branch of the subfamily salmoninae, and constituted the sister group to the genera Salmo, Salvelinus and Oncorhynchus (Crespi and Fulton 2004; Kucinski and Fopp - Bayat 2022). The estimated divergence time based on nuclear genome was similar to the previous researches based on mitochondrial genome (Crête-Lafrenière, et al 2012; Horreo 2017; Kucinski and Fopp-Bayat 2022).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations